Selective α‐Oxyamination and Hydroxylation of Aliphatic Amides - Li, Xinwei; Lin, Fengguirong; Huang, Kaimeng; Wei, Jialiang; Li, Xinyao; Wang, Xiaoyang; Geng, Xiaoyu; Jiao, Ning (Angewandte Chemie International Edition, 2017)
Compared to the α‐functionalization of aldehydes, ketones, even esters, the direct α‐modification of amides is still a challenge because of the low acidity of α‐CH groups. The α‐functionalization of N−H (primary and secondary) amides, containing both an unactived α‐C−H bond and a competitively active N−H bond, remains elusive. Shown herein is the general and efficient oxidative α‐oxyamination and hydroxylation of aliphatic amides including secondary N−H amides. This transition‐metal‐free chemistry with high chemoselectivity provides an efficient approach to α‐hydroxy amides. This oxidative protocol significantly enables the selective functionalization of inert α‐C−H bonds with the complete preservation of active N−H bond. Active duty: A general and efficient oxidative α‐oxyamination of aliphatic amides, including secondary N−H amides, was developed. This transition‐metal‐free chemistry, with high chemoselectivity, provides an efficient approach to α‐hydroxy amides. This oxidative route enables the selective functionalization of inert α‐C−H bonds with complete preservation of the active N−H bond.